2018
DOI: 10.1074/jbc.m117.812826
|View full text |Cite
|
Sign up to set email alerts
|

De novo expression of human polypeptide N-acetylgalactosaminyltransferase 6 (GalNAc-T6) in colon adenocarcinoma inhibits the differentiation of colonic epithelium

Abstract: Edited by Eric R. FearonAberrant expression of O-glycans is a hallmark of epithelial cancers. Mucin-type O-glycosylation is initiated by a large family of UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferases (GalNAc-Ts) that target different proteins and are differentially expressed in cells and organs. Here, we investigated the expression patterns of all of the GalNAc-Ts in colon cancer by analyzing transcriptomic data. We found that GalNAc-T6 was highly up-regulated in colon adenocarcinomas but absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 110 publications
6
64
0
Order By: Relevance
“…cro ARTICLE glycopeptide substrates (12,20,21), but more recently, use of isogenic cell lines with knockout (KO) and/or knock-in (KI) of individual GALNT genes coupled with the development of quantitative differential O-glycoproteomics has provided more comprehensive insight into the contributions of individual Gal-NAc-Ts to the O-glycoproteome (22)(23)(24)(25). Perhaps surprisingly, this latter approach has indicated that the nonredundant contributions of GalNAc-T isoenzymes to the O-glycoproteome appear to be minor, and the majority of O-glycosites are redundantly glycosylated among the isoforms present in a cell (22).…”
mentioning
confidence: 99%
“…cro ARTICLE glycopeptide substrates (12,20,21), but more recently, use of isogenic cell lines with knockout (KO) and/or knock-in (KI) of individual GALNT genes coupled with the development of quantitative differential O-glycoproteomics has provided more comprehensive insight into the contributions of individual Gal-NAc-Ts to the O-glycoproteome (22)(23)(24)(25). Perhaps surprisingly, this latter approach has indicated that the nonredundant contributions of GalNAc-T isoenzymes to the O-glycoproteome appear to be minor, and the majority of O-glycosites are redundantly glycosylated among the isoforms present in a cell (22).…”
mentioning
confidence: 99%
“…We selected 5 types of ppGalNac-Ts (GALNT2, GALNT3, GALNT6, GALNT12, GALNT14), as these ppGalNac-Ts have been reported to be closely associated with CRC. [27][28][29][30][31] Our analysis did not detect obvious differences in the mRNA levels of these ppGalNAc-Ts between Cosmc-overexpressing cells and the control cells ( Figure 4C). Collectively, these results suggested that aberrant O-glycosylation is unlikely the cause for Cosmc overexpression-mediated oncogenic alterations.…”
Section: Cosmc Overexpression-mediated Oncogenic Alterations Were Nmentioning
confidence: 63%
“…Interestingly, GALNT6 transcripts are upregulated in colon adenocarcinoma, correlated with a cancer‐like dysplastic growth . GALNT6 knock‐down results in increased cell‐cell adhesion and a more differentiated phenotype . In addition, GALNT6 transcription is induced by over activation of HBP in A549 pulmonary cancer cells cultured in hyperglycemic conditions .…”
Section: Discussionmentioning
confidence: 99%
“…GALNTs are more active in CRC and responsible for initiating mucin‐type O ‐Glycan synthesis, the initial product being the Tn‐antigen (Ser/Thr‐αGalNAc) . Interestingly, GALNT6 transcripts are upregulated in colon adenocarcinoma, correlated with a cancer‐like dysplastic growth . GALNT6 knock‐down results in increased cell‐cell adhesion and a more differentiated phenotype .…”
Section: Discussionmentioning
confidence: 99%